The Effect of Membrane Surface Hydrophobicity on the Performance and Water Production Cost of a Desalination Unit - Sima Rabiei; Anthony H. J. Paterson (Membranes)
Membrane pore wetting remains a significant challenge to achieving the stable operation and commercialization of membrane distillation processes. This study quantitatively assessed membrane surface hydrophobicity to investigate its impact on the performance and water production cost of an MD system. Membranes with a similar pore wetting resistance but differing in surface hydrophobicity and pore diameter were examined. A direct contact membrane distillation unit was modeled, and the water flux results were compared with laboratory experiments to validate the model. The validated model was subsequently employed to simulate a seawater desalination plant with a designed capacity of 20 m3/day. The results demonstrated that membranes with a higher surface hydrophobicity and bigger pore sizes achieved higher water flux, increasing from 0.6 kg/m2·h to 2.5 kg/m2·h, and significantly reduced water production costs from NZD$13.5/m3 to $3.9/m3. This research highlights the importance of optimizing membrane surface properties and microstructures to advance MD applications.